Do Perceiver Effects in Interpersonal Perception Predict Cooperation in Social Dilemmas? - Richard Rau; Isabel Thielmann; Simon M. Breil; Katharina Geukes; Sascha Krause; Lucie Nikoleizig; Mitja D. Back; Steffen Nestler (Collabra: Psychology, 2020)

On the Limited Generality of Air Pollution and Anxiety as Causal Determinants of Unethical Behavior: Commentary on Lu, Lee, Gino, and Galinsky (2018) - Daniel W. Heck; Isabel Thielmann; Sina A. Klein; Benjamin E. Hilbig (Psychological Science, 2020)

On the robustness of the association between Honesty-Humility and dishonest behavior for varying incentives - Sina A. Klein; Isabel Thielmann; Benjamin E. Hilbig; Daniel W. Heck (Journal of Research in Personality, 2020)

Personality and prosocial behavior: A theoretical framework and meta-analysis. - Isabel Thielmann; Giuliana Spadaro; Daniel Balliet (Psychological Bulletin, 2020)

Punishment goals in classroom interventions: An attributional approach - Mathias Twardawski; Benjamin E. Hilbig; Isabel Thielmann (Journal of Experimental Psychology: Applied, 2020)

Seeing me, seeing you: Testing competing accounts of assumed similarity in personality judgments. - Isabel Thielmann; Benjamin E. Hilbig; Ingo Zettler (Journal of Personality and Social Psychology, 2020)

The Nomological Net of the HEXACO Model of Personality: A Large-Scale Meta-Analytic Investigation - Ingo Zettler; Isabel Thielmann; Benjamin E. Hilbig; Morten Moshagen (Perspectives on Psychological Science, 2020)

Trust - Isabel Thielmann (Encyclopedia of Personality and Individual Differences, 2020)

Meta-Analytic Investigations of the HEXACO Personality Inventory(-Revised) Reliability Generalization, Self-Observer Agreement, Intercorrelations, and Relations to Demographic Variables - Morten Moshagen; Isabel Thielmann; Benjamin E. Hilbig; Ingo Zettler (ZEITSCHRIFT FUR PSYCHOLOGIE-JOURNAL OF PSYCHOLOGY, 2019)

Minimizing inequality versus maximizing joint gains: On the relation between personality traits and different prosocial motivations - Dorothee Mischkowski; Isabel Thielmann; Andreas Gloeckner (JOURNAL OF RESEARCH IN PERSONALITY, 2019)

No gain without pain: The psychological costs of dishonesty - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF ECONOMIC PSYCHOLOGY, 2019)

Nomological consistency: A comprehensive test of the equivalence of different trait indicators for the same constructs - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF PERSONALITY, 2019)

Situational Affordances for Prosocial Behaviour: On the Interaction Between Honesty‐Humility and (Perceived) Interdependence - Simon Columbus; Isabel Thielmann; Daniel Balliet (European Journal of Personality, 2019)

Daring dishonesty: On the role of sanctions for (un)ethical behavior - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF EXPERIMENTAL SOCIAL PSYCHOLOGY, 2018)

Foreign language reduces the longevity of the repetition-based truth effect - Lena Nadarevic; Sarah Plier; Isabel Thielmann; Stefania Daranco (ACTA PSYCHOLOGICA, 2018)

Is it all about the money? A re-analysis of the link between Honesty-Humility and Dictator Game giving - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF RESEARCH IN PERSONALITY, 2018)

Lead Us (Not) into Temptation: Testing the Motivational Mechanisms Linking Honesty-Humility to Cooperation - Benjamin E. Hilbig; Pascal J. Kieslich; Felix Henninger; Isabel Thielmann; Ingo Zettler (EUROPEAN JOURNAL OF PERSONALITY, 2018)

The brighter the light, the deeper the shadow: Morality also fuels aggression, conflict, and violence - Robert Boehm; Isabel Thielmann; Benjamin E. Hilbig (BEHAVIORAL AND BRAIN SCIENCES, 2018)

Think it through before making a choice? Processing mode does not influence social mindfulness - Dorothee Mischkowski; Isabel Thielmann; Andreas Gloeckner (JOURNAL OF EXPERIMENTAL SOCIAL PSYCHOLOGY, 2018)

Who lies? A large-scale reanalysis linking basic personality traits to unethical decision making - Daniel W. Heck; Isabel Thielmann; Morten Moshagen; Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2018)

Between me and we: The importance of self-profit versus social justifiability for ethical decision making - Sina A. Klein; Isabel Thielmann; Benjamin E. Hilbig; Ingo Zettler (JUDGMENT AND DECISION MAKING, 2017)

Between me and we: The importance of self-profit versus social justifiability for ethical decision making. - Sina Klein; Isabel Thielmann; Benjamin E. Hilbig; Ingo Zettler (Judgment and Decision Making, 2017)
Current theories of dishonest behavior suggest that both individual profits and the availability of justifications drive cheating. Although some evidence hints that cheating behavior is most prevalent when both self-profit and social justifications are present, the relative impact of each of these factors is insufficiently understood. This study provides a fine-grained analysis of the trade-off between self-profit versus social justifiability. In a non-student online sample, we assessed dishonest behavior in a coin-tossing task, involving six conditions which systematically varied both self-profit and social justifiability (in terms of social welfare), such that a decrease in the former was associated with the exact same increase in the latter. Results showed that self-profit outweighed social justifiability, but that there was also an effect of social justifications.

Does everyone have a price? On the role of payoff magnitude for ethical decision making - Benjamin E. Hilbig; Isabel Thielmann (Cognition, 2017)
Most approaches to dishonest behavior emphasize the importance of corresponding payoffs, typically implying that dishonesty might increase with increasing incentives. However, prior evidence does not appear to confirm this intuition. However, extant findings are based on relatively small payoffs, the potential effects of which are solely analyzed across participants. In two experiments, we used different multi-trial die-rolling paradigms designed to investigate dishonesty at the individual level (i.e., within participants) and as a function of the payoffs at stake - implementing substantial incentives exceeding 100€. Results show that incentive sizes indeed matter for ethical decision making, though primarily for two subsets of “corruptible individuals” (who cheat more the more they are offered) and “small sinners” (who tend to cheat less as the potential payoffs increase). Others (“brazen liars”) are willing to cheat for practically any non-zero incentive whereas still others (“honest individuals”) do not cheat at all, even for large payoffs. By implication, the influence of payoff magnitude on ethical decision making is often obscured when analyzed across participants and with insufficiently tempting payoffs.

On Measuring the Sixth Basic Personality Dimension: A Comparison Between HEXACO Honesty-Humility and Big Six Honesty-Propriety - Isabel Thielmann; Benjamin E. Hilbig; Ingo Zettler; Morten Moshagen (ASSESSMENT, 2017)

Seeing is Knowing: On the Predictive Accuracy of Self- and Informant Reports for Prosocial and Moral Behaviours - Isabel Thielmann; Johannes Zimmermann; Daniel Leising; Benjamin E. Hilbig (EUROPEAN JOURNAL OF PERSONALITY, 2017)

Should Versus Want: On the Relative Contribution of Injunctive Norms and Preferences on Trust Decisions - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF BEHAVIORAL DECISION MAKING, 2017)

Anonymity and incentives: An investigation of techniques to reduce socially desirable responding in the Trust Game - Isabel Thielmann; Daniel W. Heck; Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2016)

The two faces of cooperation: On the unique role of HEXACO Agreeableness for forgiveness versus retaliation - Benjamin E. Hilbig; Isabel Thielmann; Sina A. Klein; Felix Henninger (JOURNAL OF RESEARCH IN PERSONALITY, 2016)

Who Does (Not) Participate in Intergroup Conflict? - Isabel Thielmann; Robert Boehm (SOCIAL PSYCHOLOGICAL AND PERSONALITY SCIENCE, 2016)

Different Games for Different Motives: Comment on Haesevoets, Folmer, and Van Hiel (2015) - Isabel Thielmann; Robert Böhm; Benjamin E. Hilbig (European journal of personality, 2015)

From Honesty-Humility to fair behavior - Benevolence or a (blind) fairness norm? - Benjamin E. Hilbig; Isabel Thielmann; Johanna Wührl; Ingo Zettler (Personality and Individual Differences, 2015)

From personality to altruistic behavior (and back): Evidence from a double-blind dictator game - Benjamin E. Hilbig; Isabel Thielmann; Johanna Hepp; Sina A. Klein; Ingo Zettler (Journal of Research in Personality, 2015)

Now you see it, now you don't: Explaining inconsistent evidence on gender stereotyping of newborns - Isabel Thielmann; Edgar Erdfelder; Dagmar Stahlberg (EUROPEAN JOURNAL OF SOCIAL PSYCHOLOGY, 2015)

The Traits One Can Trust: Dissecting Reciprocity and Kindness as Determinants of Trustworthy Behavior - Isabel Thielmann; Benjamin E. Hilbig (PERSONALITY AND SOCIAL PSYCHOLOGY BULLETIN, 2015)

Trust: An integrative review from a person-situation perspective. - Isabel Thielmann; Benjamin E. Hilbig (Review of General Psychology, 2015)

Trust in me, trust in you: A social projection account of the link between personality, cooperativeness, and trustworthiness expectations - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF RESEARCH IN PERSONALITY, 2014)

WILLING TO GIVE BUT NOT TO FORGIVE: BORDERLINE PERSONALITY FEATURES AND COOPERATIVE BEHAVIOR - Isabel Thielmann; Benjamin E. Hilbig; Inga Niedtfeld (JOURNAL OF PERSONALITY DISORDERS, 2014)

WILLING TO GIVE BUT NOT TO FORGIVE: BORDERLINE PERSONALITY FEATURES AND COOPERATIVE BEHAVIOR - Isabel Thielmann; Benjamin E. Hilbig; Inga Niedtfeld (JOURNAL OF PERSONALITY DISORDERS, 2014)

The HEXACO-100 Across 16 Languages: A Large-Scale Test of Measurement Invariance - Isabel Thielmann; Nazar Akrami; Toni Babarovic; Amparo Belloch; Robin Bergh; Antonio Chirumbolo; Petar Colovic; Reinout E. de Vries; Daniel Dostal; Marina Egorova; Augusto Gnisci; Timo Heydasch; et al. (JOURNAL OF PERSONALITY ASSESSMENT)